The Role of Guidance and Counseling Service on Academic Performance among Students of Umar Suleiman College of Education, Gashua, Yobe State, Nigeria - Kyauta, Amadu Muktar A.; Shariff, Yusuf Abdullahi; Garba, Hafsat Suleiman (NIU Journal of Humanities, 2018)
This study was conducted in the month of March to August 2017 to examine the Role of Guidance and Counseling services on academic performance among students of Umar Suleiman College of Education, Gashua, Yobe State, Nigeria. The study used descriptive survey study designs with both qualitative and quantitative approaches. Purposive and simple random sampling techniques were employed. Data was collected using self-administered questionnaire from 100 students across NCE 1,NCE 2 and NCE 3 ; and interview guide to 5 teachers/counselors who are directly involved in Guidance and Counseling services. The data was analyzed in SPSS Version 6using the frequency percentage, Mean and Standard Deviation distribution tables. The findings revealed that the Guidance and Counseling services offered in the College included: academic, health, moral, and spiritual matters, the services offered proved to be moderately effective in influencing studentsâ€™ study habits and much improvement in academic performance. It was concluded that accessing Guidance and Counseling services has an effect in shaping studentsâ€™ attitude towards studies and career choice as well as improvement in general academic performance. Based on this findings, the following recommendation were made Guidance and Counseling services should be intensified in schools by appointing full time  Counselors in each schools. Teachers and school Guidance Counselors should also collaboratively guide students on how to develop good study habits, thereby enhancing their academic performance and success. Student should be encouraged to seek for guidance and counseling in their future career.